A simple and industrially scalable process for recycling hexaferrite ceramic magnets - Alba Berja; Daniel Casaleiz; Cecilia Granados-Miralles; Karla Kosmač; Boris Saje; Tina Frangež; Slavko Dvoršak; Zoran Samardžija; Benjamin Podmiljšak; Jose Francisco Fernández; Adrián Quesada (Open Ceramics)
The demand for hexaferrite (BaFe12O19/SrFe12O19) permanent magnets is expected to rise in the next 5–10 years due to their potential as a sustainable alternative to rare-earth magnets. Currently, less than 1 % of recycling of permanent magnets occurs worldwide. This study presents a successful method for recycling strontium ferrite magnets from end-of-life household appliances, fabricating recycled bonded magnets as a first step to implement a circular economy in the value chain. This industrially scalable method optimizes comminution and annealing of recovered ceramic magnets, yielding powders with particle sizes below 2 µm. Thermal treatment at 900–1000 °C recovers competitive magnetic properties. A pilot batch of recycled hexaferrite bonded magnets, produced via injection moulding, exhibited excellent mechanical and magnetic properties, with coercivity Hcj of 190.1 kA/m, remanent polarization Jr of 234.3 mT, and maximum energy product (BH)max of 10.4 kJ/m³, comparable to commercial ferrite bonded magnets.